Best practices in grievance handling mechanism: a study in Kerala - Pradeep, Adithi; Niha, Alfiya; Gopan, Gopika; Kumar K, Vinod (International Journal of Engineering and Technology, 2018)
In the present world, grievance in workplace is a common phenomenon. Grievance handling is of great importance to the human resource management sector as it will directly affect the work force of the company; unless it is taken care of in the right time, in the right manner. This study is focused on methods to implement this effectively and the responses of various employees in HOMCO have been taken for the assessment of the current system. A study on grievance handling mechanism was done at the Kerala State Homoeopathic Co-Operative Pharmacy (HOMCO). The HOMCO is engaged in manufacturing and sale of Homoeopathic Medicines. It is the sole supplier of Homoeopathic Medicines to hospitals since 1980. â€œGrievance Handling Mechanismâ€ at The Kerala State Homoeopathic Co-Operative Pharmacy Limited is undertaken to make an exploration into the grievances faced by employees and to find possible solutions to increase the efficiency of the system.Â Â